INTELLECTUAL MONITORING SPINDLE NODE ON BASE OF THE FUZZY LOGIC - E.V. REMIZOV; E.A. LUKIYANOV (Вестник Донского государственного технического университета, 2018)
In article there are brought the cardinal principles of creation of the spindle node condition monitoring system of turning unit based on fuzzy-logic. There will be analyzed different factors, influencing upon accuracy of the processing product on machine tool with CNC and are chose the main influence. The fuzzy-logic monitoring system and experimental checking data of the result of the designed system functioning will be presented.